Pineal adrenal-thyroid relationship under thermal stress: Effect on circulating levels of thyroid hormones in goat - SEJIAN, V; SRIVASTAVA, R S; VARSHNEY, V P (The Indian Journal of Animal Sciences, 2011)
The purpose ofthe investigation was to examine the effect of melatonin on circulating thyroid hormones in the absence of glucocorticoids in female goats under short-term thermal stress. Female goats (6) were used in the study and they served as self controls prior to start of the experiment. Thermal stress significantly increased the T4 level while nonsignificantly increasing T3â€¢ Chemical adrenalectorny significantly reduced the plasma levels of the T4 and T3 â€¢ Melatonin further reduced significantly the levels of thyroid hOrlTIOnes. The obtained result suggests an endocrine relationship existing between pineal, adrenal and thyroid glands to control the level of circulating thyroid hormones under thennal stress. Â